KAPASITAS APRON DI BANDAR UDARA INTERNASIONAL ADISUTJIPTO YOGYAKARTA - Reni Dian Octaviani; Winy Nuwita; Agus Setiawan (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of this study is to investigate parking stand on apron capacity in occupied time. The method of this study was field research and library research. The data was analyzed by using queue theory. The result of this study shows that P, as a level of service facility in occupied time, is 83.33%. Po, probability of 0 planes in queue, is 80%. Lq (average planes in queue in occupied time) is 2.44 planes each hour. Ls (number of planes in total system in occupied time)is 15.77 planes each hour. Wq (average time in queue) in occupied time is 15 minutes. Ws (the average time in queue total system) in occupied timeis 95 minutes. Based on the data, parking stand at international airport Adisutjipto Yogyakarta is not optimal because the number of flight is too crowded in occupied time. It causes the queue of planes at the airport.